Rahasia di balik pembelian: Bagaimana E-WOM dan brand image mempengaruhi keputusan pembelian Skincare di Shopee - Sah, Nurul Alfadiza; Amin, Andi Mustika; Musa, Muhammad Ichwan; Aswar, Nurul Fadilah; Hasdiansa, Ilma Wulansari (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This study aimed to determine the effect of electronic word of mouth (E-WOM) and brand image on the purchase intention for Avoskin skincare products on the Shopee marketplace. The participants in this study were active female students at the Faculty of Economics and Business, Makassar State University, for the Class of 2020. The sample comprises 100 respondents. A questionnaire was used for data collection. The data analysis technique used was multiple linear regression analysis using the Statistical Product and Service Solution (SPSS). The results of this study indicate that electronic word of mouth and brand image both partially and simultaneously have a positive and significant effect on purchase intention. The novelty of this study was the focus on the effect of electronic WOM and brand image on the purchase intention of Avoskin skincare products on Shope using a sample of female students at Makassar State University. The theoretical implications enrich the literature on the factors that influence purchase intention on e-commerce. Practical implications help Avoskin develop effective marketing strategies for Shopee by managing positive reviews and building a strong brand image. Keywords: Electronic word of mouth, brand image, purchase intention